Moral Issues in the Recent History of the Bulgarian Orthodox Church - Nikolova, Ivelina (Occasional papers on religion in Eastern Europe, 2014)
Over the past centuries Bulgarian people experienced severe religious and ethnic threats due to which they have developed defense mechanisms and a strong sense of sympathy for persecuted ethnic and social groups. In recent history, this reflex was manifested most clearly in the behavior of the Bulgarian Orthodox Church in defense of the Bulgarian Jews. At the same time two other events, however, reveal its controversial image that caused it a severe damage. In recent years, many Bulgarians are seeking the moral dimensions of these phenomena that influence the spirituality and morality of the younger generations.